Analisis Permintaan Beras Di Kabupaten Boyolali Tahun 2000-2014 - Prastowo, Sandi Hendra, Didit Purnomo, SE., M.Si (2016)
This study aimed to analyze the influence of the factors the price of rice, the price of corn, egg prices, population and income of the population against the demand for rice in Boyolali and analyze the elasticity of demand for rice in Boyolali. Testing the hypothesis in this study using linear regression analysis with Ordinary Least Square method (OLS). Based on the survey results revealed that the price of rice, the price of corn, the price of eggs, population, and income residents jointly significant effect on demand for rice in Boyolali. In the analysis showed that the variables of population and income of the population have a significant effect on demand for rice in Boyolali confidence level of 99%, while the variable price of rice, the price of corn, the price of eggs has no significant effect on the demand for rice in the district of Klaten. Rice demand is inelastic because the coefficient of elasticity 0 <Ep <1, which means that the amount of rice that the requested change to a smaller percentage than the change in the price of rice.